Implementation of safeguard measures in digital trade to protect African domestic industries and platforms - Rotich, Nelly Chepngetich (University of Pretoria, 2025)
As technology continues to advance, more trade is moving online. The increase in digital trade brings with it both opportunities and challenges in the international trade field. The increase in digital trade could for instance result in a spike in digital trade imports which may subsequently cause or threaten to cause serious injury to domestic industries and platforms dealing in like or directly substitutable digital data/content and services. This would necessitate the application of safeguard measures to avert any such serious injury or threat to serious injury caused to the domestic industries and platforms. The procedure for applying safeguard measures to digital trade currently is unclear. The current legal framework on safeguard measures does not apply to digital trade despite increased digital trade over the years. Thus, this study explores the prospects and practical challenges relating to safeguard measures’ application to digital trade with a specific focus on African domestic industries and platforms. While domestic industries and platforms in any part of the world could be affected by surges in digital trade imports, Africa is in a precarious position. Intra-Africa digital trade volumes could be increased and disadvantages of African domestic industries and platforms by surges in digital trade imports could be prevented through regulation and judicious use of safeguard measures. This study established the need to regulate to tap into the potential of digital trade and prevent African industries and platforms from falling behind and from the disadvantage of market dominance by big techs from outside Africa. In conclusion, the study noted legal and institutional gaps in the application of safeguard measures to digital trade. The study has recommended that specific institutions at the global, continental and national levels take necessary actions to build a clear and robust framework for safeguard measures in digital trade.
Keywords: Digital trade; International Trade

The use of blockchain for collecting value-added tax on online cross-border trade in digital goods - Kabwe, Ruddy Kapasula (University of Pretoria, 2024)
The collection of value-added tax from the cross-border supply of digital goods remains a challenge for tax authorities around the world. South Africa is no different. The traditional methods of collecting VAT from the supply of digital goods relies on the honesty of the consumer and on the supplier to account for and remit VAT to the tax authorities in the jurisdiction where the goods are consumed. The traditional collection models are often unreliable, inefficient, burdensome, and expensive for the consumers and the suppliers. The adoption of blockchain technology as a model to collect VAT on the cross-border supply of digital goods has the potential to alleviate the compliance burden on consumers and suppliers of digital goods, improve the efficiency of tax administration, and reduce VAT fraud. Importantly, blockchain technology can create trust between tax authorities, suppliers of digital goods, and consumers. This thesis critically discusses the advantages and disadvantages of implementing blockchain technology for the collection of VAT on the cross-border supply of digital goods in South Africa. This thesis unpacks the consideration factors for policymakers in the implementation of blockchain technology for the collection of VAT on cross-border trade in digital goods. The thesis makes recommendations for the South African VAT Act to be amended to make provision for the collection of VAT by utilising blockchain technology.
URI: https://repository.up.ac.za/handle/2263/97005
Keywords: Anonymisation; Blockchain technology; Decentralisation; Digital goods; Private blockchain; Smart contracts; Taxpayer privacy; Value-added tax

Developing a regulatory framework for electronic commerce in the Southern African Development Community: the prospects and challenges - Chimeri, Vongai (University of Fort Hare; Faculty of Law, 2023)
Keywords: Community law; E-commerce; Electronic Commerce; Electronic Transactions; Intra-regional trade; Regional integration; SADC; SADC Model Law

Abuse of dominance and the Internet : an assessment of the South African Regulatory Framework - Koornhof, Pieter Gerhardus Jacobus (Stellenbosch University, 2021)
While electronic commerce in South Africa is still comparatively small, it is growing rapidly. The advent of the internet has potentially fundamental impacts on business and the law both locally and internationally. It is submitted the free competition on the internet is important and will continue to be so in the future. The research in this thesis relates to the rise of so-called internet monopolies (such as Google, Facebook and Amazon) and its implications for competition law enforcement. A particularly problematic aspect of the products provided by some of these companies is that their products and services are ostensibly free to consumers. This thesis examines whether the traditional model for the regulating abuse of dominance would be effective in the instance where such an internet monopoly is charged with a contravention under South African competition law. The research and analysis in the thesis are effectively divided into three parts. The first considers whether abuse of dominance related to the internet deserves closer analysis and also assesses the purposes of competition law and how these are changing (or should change) in the light of new technology and markets. The second part deals with abuse of dominance both generally and specifically in relation to the internet. In this context, the thesis considers how harms may manifest and how dominance may be determined in the context of the internet. The final part considers specific issues that may be problematic in light of the internet. The interrelationship between intellectual property and competition law is analysed, along with aspects pertaining to the assertion of jurisdiction, the nature of competition law enforcement and the extent to which different jurisdictions may (and/or should) cooperate in dealing with abuse of dominance on the internet. The thesis submits that the South African legislative framework for regulating abuse of dominance on the internet is broadly fit for purpose, but that there is a need for developing new approaches and policy within that framework. It contributes to the existing body of knowledge and discourse by providing a comprehensive overview of the regulatory framework in South Africa, informed by comparative analysis; by applying this in a new context (hitherto under-researched in the South African context), and by offering concrete suggestions to frame policy and approach.
URI: http://hdl.handle.net/10019.1/123687
Keywords: Competencia; Competition law; E-commerce; Electronic commerce; Internet monopolies; South African competition law; South African legislative Framework

The regulation of unsolicited electronic communications (SPAM) in South Africa : a comparative study - Tladi, Sebolawe Erna Mokowadi (University of South Africa, 2017)
The practice of spamming (sending unsolicited electronic communications) has been dubbed “the scourge of the 21st century” affecting different stakeholders. This practice is also credited for not only disrupting electronic communications but also, it overloads electronic systems and creates unnecessary costs for those affected than the ones responsible for sending such communications. In trying to address this issue nations have implemented anti-spam laws to combat the scourge. South Africa not lagging behind, has put in place anti-spam provisions to deal with the scourge. The anti-spam provisions are scattered in pieces of legislation dealing with diverse issues including: consumer protection; direct marketing; credit laws; and electronic transactions and communications. In addition to these provisions, an Amendment Bill to one of these laws and two Bills covering cybercrimes and cyber-security issues have been published. In this thesis, a question is asked on whether the current fragmented anti-spam provisions are adequate in protecting consumers. Whether the overlaps between these pieces of legislation are competent to deal with the ever increasing threats on electronic communications at large. Finally, the question as to whether a multi-faceted approach, which includes a Model Law on spam would be a suitable starting point setting out requirements for the sending of unsolicited electronic communications can be sufficient in protecting consumers. And as spam is not only a national but also a global problem, South Africa needs to look at the option of entering into mutual agreements with other countries and organisations in order to combat spam at a global level.
Keywords: Anti-spam laws; Commercial electronic messages; Consumer law; Direct marketing; Electronic commerce; Electronic communications; Electronic mail (e-mail); International cooperation; Right of privacy; Spam (Electronic mail); Telemarketing; Unsolicited commercial communications; Unsolicited electronic communications

Disputes in the Digital era : the evolution of dispute resolution and the model ODR system - Lekkas, Zissis (Université Toulouse 1 Capitole, 2015)
Le sujet de la thèse est la résolution en ligne des litiges (ODR) et l'objectif de la thèse est de proposer un modèle de système ODR basé sur l'expérience du mouvement de résolution des différends. ODR n’est pas un phénomène isolé de ces derniers temps, mais en raison de l'évolution des conflits et la résolution des différends. Initialement, les différends survenus entre les parties à la proximité géographique et pour laquelle les tribunaux traditionnels sont le principal moyen de résolution. Cependant, comme les gens ont commencé à voyager de plus grandes distances et de communiquer de loin, les conflits ont évolué comme ils ont augmenté en nombre, sont devenus frontière plus complexe et de plus en plus transversale. Résolution des différends évolués en règlement des différends parallèle et alternatif (ADR) a été utilisée. Cependant, les conflits ont évolué une fois de plus quand le monde est entré dans l'ère numérique. Non seulement les conflits sont devenus encore plus transfrontalier, mais de nouveaux conflits sont apparus qui proviennent exclusivement dans le cyberespace. Afin de satisfaire aux exigences de l'ère numérique, la résolution des différends fit sortir le concept de l'ODR. ODR est née de la combinaison de l'ADR et de la technologie de l'information et de la communication (TIC) de l'ère numérique. D'autres moyens de règlement des différends ont été transférés dans le monde virtuel et ont donné naissance à la résolution des litiges en ligne. ADR et ODR sont examinés largement, et l'examen comprend leurs concepts, leur origine, les principales formes de négociation, de médiation et d'arbitrage et leurs équivalents en ligne, ainsi que leurs avantages et leurs inconvénients. La thèse illustre l'évolution des conflits et la résolution des différends de l'ère analogique, lorsque la résolution des différends était face à face, à l'ère du numérique, lorsque les différends sont réglés dans le cyberespace. Il démontre que l'ODR est une nécessité de l'ère numérique, mais aussi qu'il a le potentiel pour être un moyen révolutionnaire, efficace et réussi à résoudre les différends; d'une manière qui sera l'avenir de la résolution des différends. Sur la base de l'expérience accumulée par l'examen de l'évolution de la résolution des différends et sur ? Lla base des conclusions tirées, la thèse formule une proposition pour le système ODR. La thèse décrit le système ODR, de son processus en trois étapes et la nécessité de l'arbitrage en ligne, sur le réseau ODR, la régulation du système ODR, l'architecture technologique des fournisseurs ODR, leur financement, ainsi que les mesures nécessaires de la sensibilisation et la confiance afin que ODR remplit son plein potentiel.
Keywords: Arbitrage; Arbitragem; Arbitration; Commerce électronique; Modes électroniques de règlement des litiges; Online Dispute Resolution; Système ODR

International taxation of cross-border digital commerce - Kadikov, Artem (University of Oxford, 2015)
This thesis discusses jurisdiction to tax cross-border digital commerce. The primary objective is to consider the reasons for the erosion of jurisdictional links, or nexus, between countries and taxpayers' digital activities and evaluate possible solutions for addressing such nexus erosion. Whilst it is argued that digital commerce is impossible to ring-fence due to digital technologies transcending all industries, the main focus of this research is on automated business models as case studies for the broader tax issues applicable across the entire digital economy. Using cloud computing, online advertising and e-tailing models as examples of digital commerce in the narrow sense, this thesis demonstrates that the proxies for establishing jurisdictional nexus have become increasingly fluid, thereby challenging the traditional international tax regimes for profits and consumption taxation. Numerous policy solutions have been proposed in order to rectify nexus erosion, including global and territorial tax models. Unlike the previous research in this area, this thesis focuses on the nexus elements of such proposals and assesses their viability in the light of the wider Internet governance jurisprudence. Global tax solutions, such as global e-commerce taxes and formulary apportionment, are analysed in the context of the international governance regime for the technical Internet infrastructure. Territorial virtual tax solutions, such as virtual permanent establishments, withholding taxes and destination cash flow taxes, are considered in the light of the Internet jurisprudence on the 'effects' and 'targeting' nexus standards. It is argued that, given the lack of technical and political infrastructure, none of the proposed routes would be viable from a practical perspective in the near future. It is concluded, therefore, that a practical solution would involve retaining the traditional profits and consumption tax models, whilst testing a narrow version of the digital targeting nexus standard as a backstop anti-abuse measure. It is envisaged that the limited anti-avoidance provision would subsequently pave the way for a comprehensive long-term solution, as digitisation continues to transform global commerce.
Keywords: Corporations; Digital commerce taxation; Double taxation; E-commerce taxation; Electronic commerce; International Trade; International business enterprises; Internet governance; Internet jurisdiction; Internet taxation; Jurisdiction to tax; Taxation

The collection of value added tax on online cross-border trade in digital goods - Van Zyl, Stephanus Phillipus (University of South Africa, 2013)
Technological advances have had a major impact on traditional retail shopping changing it from a physical undertaking to a completely digitised experience where consumers buy digital media online. VAT systems that do not specifically provide for, or which have not been adapted to cope with, technology-driven advances, generally do not provide for the adequate levying and collection of VAT on cross-border digital trade. The South African VAT system is no different. The taxation of e-commerce should not artificially advantage or disadvantage e-commerce over comparable traditional commerce, or unnecessarily hinder the development of e-commerce. This thesis determines whether the South African VAT Act 89 of 1991 in its current form, can be applied adequately to raise and collect VAT on cross-border digital transactions. Where shortcomings in the VAT Act are identified, the harmonised VAT rules of the European Union (EU), together with the Organisation for Economic Cooperation and Development (OECD) proposals on consumption taxes, are analysed and discussed to seek possible solutions and make recommendations.
Keywords: Anonymising technology; B2B transactions; B2C transactions; BIT-rate tax; Banker-customer confidentiality; Blocked VAT account; Consumption taxes; Cross-border digital trade; Electronic commerce; Electronically supplied services; European Union; European Union countries; Fractionated VAT; OECD; South Africa; Taxation; VAT collection model; Value-added tax

Análisis y modelización de la adopción de los sistemas de recomendación en el comercio electrónico - Cabal Cruz, Claudia Constanza (Universidad Internacional de Andalucía, 2013)
Tesis doctoral (Lectura 07/02/2013). Director: Francisco José Martínez López (Universidad de Granada). Tribunal: Martínez López, Francisco José, Univ. de Huelva, presidente; Padilla Meléndez, Antonio (secretario); Ortigueira Sánchez, Manuel (vocal); Luna Huertas, Paula (vocal); García Ordaz, María Mercedes (vocal). Se puede afirmar que la historia de las relaciones entre los individuos y las organizaciones se divide en dos, antes y después de la aparición de Internet, la penetración de los PC y de la banda ancha. En el campo organizacional, las Tecnologías de la Información y las Comunicaciones (TIC), se refieren al amplio espectro de tecnologías de base de los Sistemas de Información, y que se constituye en un importante recurso, que facilita la continua adaptación del Sistema de Información a los cambios internos y del entorno. La aplicación de los sistemas de información a las actividades organizacionales, caso concreto que nos interesa, el marketing, se constituye en una herramienta para que la empresa se mantenga competitiva en el mercado. Las relaciones de intercambio desarrolladas en los mercados electrónicos posibilitan la comunicación bidireccional entre las partes y entre cada una de ellas y el propio medio, exigiendo a las organizaciones implementar un marketing interactivo en términos de producto, precio, distribución y comunicación, en el que consumidor dirija el proceso de intercambio. El desarrollo del comercio en los mercados electrónicos y las aplicaciones de los sistemas de información al marketing, han tomado características del comercio tradicional y han sido adaptadas al electrónico, caso específico la adaptación que han realizado una gran cantidad de empresas comerciales en la Web a las recomendaciones a sus usuarios a través de los sistemas de recomendación (RS), entendidos como sistemas que realizan recomendaciones de productos que están buscando, o basadas en sus gustos o preferencias. Este es tema central de este trabajo, pero no enfocado a su parte técnica, sino a la comprensión de los factores que explican el comportamiento online de los consumidores frente a los RS de determinada website (WS), por lo que se propone un modelo teórico, sustentado por once hipótesis principales y otras subordinadas, la cuales son el resultado de la integración reflexiva de la Teoría de la Acción Razonada, de la adaptación Trust-TAM y de la Teoría del Comportamiento Planeado. Del análisis y corroboración del modelo, se puede concluir que el proceso de adopción del sistema de recomendación de cierto website se conforma sobre la base que a) el usuario percibe la opinión de otros con respecto al uso de los sistemas de recomendación en general y del particular de un determinado website; b) el grado de confianza que le merece al consumidor la interacción e información proporcionada por el sistema de recomendación; c) la percepción de utilidad de uso del sistema de recomendación que tiene su usuario; y d)la actitud del individuo hacia el sistema de recomendación de un website particular.

The legal and institutional framework for the enforcement of online consumer arbitration awards: evidence from Australia and Sri Lanka - Kananke, Chinthaka Liyanage (La Trobe University, 2012)
Keywords: Australia; Commercial law; Conflict of laws; Consumer protection; Dispute resolution; Electronic commerce; Sri Lanka